2011
DOI: 10.1111/j.1365-2842.2011.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal measurement method can affect SEMG activity during occlusion

Abstract: Occlusal indicators are widely used in dental treatment to measure tooth contacts that occur during occlusion. However, the presence of an indicator may affect the mechanics of occlusion and lead to invalid tooth contact data. The objective of this study was to determine the effect of four indicators (Parkell, silk, T-Scan(®) sensor and paper) on surface electromyography (SEMG) activity during occlusion. Twenty-three subjects performed strong bites and maximum clenches onto the four indicators and natural dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 16 publications
(26 reference statements)
3
26
0
5
Order By: Relevance
“…Our findings are substantially in agreement with the investigations of Forrester et al (Forrester et al , 2011): to the best of our knowledge, this is the only study that applied SEMG to reveal whether occlusal media might affect neuromuscular activity. According to the above-mentioned research, articulating paper of 200µm…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are substantially in agreement with the investigations of Forrester et al (Forrester et al , 2011): to the best of our knowledge, this is the only study that applied SEMG to reveal whether occlusal media might affect neuromuscular activity. According to the above-mentioned research, articulating paper of 200µm…”
Section: Discussionsupporting
confidence: 93%
“…Forrester et al also suggested that some specific material properties, like plasticity or stiffness, are able to modify the neuromuscular activity (Forrester et al , 2011): the validity of tooth contact registration appears to be affected not simply by indicator thickness but also by several other physical variables, or by the ability of the media to conform/adapt to the occluded surfaces. In our experiment a change from 200µm to 40µm, in fact, did not produce a significant effect on masseter or temporalis POC median values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diese kann zu einer Beeinflussung der habituellen Okklusion führen. So folgerten Forrester et al [7] aufgrund eines gemessenen Einflusses von Okklusionsindikatoren aus Papier und T-Scan-Folien auf die Werte der Oberflächenmyographie während der Okklusion, dass die Verwendung dieser Indikatoren sich auf die Okklusion auswirken könne. Die Dicke der T-Scan-Folien liegen mit einer Dicke von 100 µm im mittleren Bereich der aktuell in der zahnärztlichen Behandlung verwendeten Folien µm; [15]).…”
Section: Diskussionunclassified
“…Es ist anzustreben diese Dicke durch weitere Entwicklung zu reduzieren, doch dies ist aufgrund der kraftregistrierenden in die Folie eingebetteten Leitungsbahnen zum jetzigen Zeitpunkt noch nicht möglich. Ein weiterer Aspekt liegt in der Position [7] concluded that the use of these indicators may affect occlusion after having observed a measurable influence of occlusion indicators consisting of paper and T-scan films on surface electromyography values during occlusion. At 100 µm, the thickness of the T-Scan films lies within the average thickness range of films now used in dental practices µm) [15].…”
Section: Diskussionunclassified